EFEKTIVITAS PENGGUNAAN MODUL BERBASIS PROJECK BASED LEARNING DALAM PEMBELAJARAN TEKNOLOGI ALAT BERAT - Rido Putra; Wawan Purwanto; Hasan Maksum; Dedy Irfan; Muslim Muslim; Hendra Dani Saputra (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2022)
Learning requires support from a reliable media, one of which can be a learning module. Based on several previous studies regarding the module, there are still some shortcomings from the module under study. So that further development of the given module is needed by adding the contents of the module using the project. This study aims to examine the development of heavy equipment technology modules including validity tests, practicality tests and project-based effectiveness tests. This research is included in Research and Development (R&D) research. The model used in this study uses the ADDIE principle, the data collection method is through questionnaires and learning outcomes tests, the data analysis is processed using a quantitative approach and described through a qualitative approach to conclude the research results, the research subjects consist of lecturers and students. The results of the research conducted on the development of PjBl-based modules meet the feasibility, in terms of aspects of validity, practicality and effectiveness. The results of the analysis of the validity aspect are 89.07% very valid criteria, the average practicality aspect is 87.92% very practical criteria. The effectiveness aspect is seen from the knowledge test and project test. The test results on 30 students have an average score of 86.67% in the good category and in the field of skills (projects) of 86.67% very high criteria. The conclusion is that the development of PjBL-based modules is able to attract attention and make students understand the material and be able to work together in groups.